Issues of Participatory Digital Theatre. Reflections on Three Forms Developed during the Pandemic (Itinera, 2021)
This article studies three participatory theatre-forms on zoom. It aims at analyzing what kind of participation is possible in the space of video-conferencing, which is both located in a private room and at a distance. These theatres seem able to interpellate the audience on a cognitive as well as a social and even an affective level. Each apparatus focuses on a different dimension, be it imagination, empathy or criticality. Yet the interactions result in an experience that is anchored in the social and sensitive subjectivity. The enable the audience to reflect on an array of issues that are far from limited to the pandemic.
Keywords: Participatory art, Zoom Theatre, Criticality, Experience, Imagination